Current and future pharmacological therapies for managing cirrhosis and its complications. - Kockerling,D; Nathwani,R; Forlano,R; Manousou,P; Mullish,BH; Dhar,A (World J Gastroenterol, 2019)
Due to the restrictions of liver transplantation, complication-guided pharmacological therapy has become the mainstay of long-term management of cirrhosis. This article aims to provide a complete overview of pharmacotherapy options that may be commenced in the outpatient setting which are available for managing cirrhosis and its complications, together with discussion of current controversies and potential future directions. PubMed/Medline/Cochrane Library were electronically searched up to December 2018 to identify studies evaluating safety, efficacy and therapeutic mechanisms of pharmacological agents in cirrhotic adults and animal models of cirrhosis. Non-selective beta-blockers effectively reduce variceal re-bleeding risk in cirrhotic patients with moderate/large varices, but appear ineffective for primary prevention of variceal development and may compromise renal function and haemodynamic stability in advanced decompensation. Recent observational studies suggest protective, haemodynamically-independent effects of beta-blockers relating to reduced bacterial translocation. The gut-selective antibiotic rifaximin is effective for secondary prophylaxis of hepatic encephalopathy; recent small trials also indicate its potential superiority to norfloxacin for secondary prevention of spontaneous bacterial peritonitis. Diuretics remain the mainstay of uncomplicated ascites treatment, and early trials suggest alpha-adrenergic receptor agonists may improve diuretic response in refractory ascites. Vaptans have not demonstrated clinical effectiveness in treating refractory ascites and may cause detrimental complications. Despite initial hepatotoxicity concerns, safety of statin administration has been demonstrated in compensated cirrhosis. Furthermore, statins are suggested to have protective effects upon fibrosis progression, decompensation and mortality. Evidence as to whether proton pump inhibitors cause gut-liver-brain axis dysfunction is conflicting. Emerging evidence